Implementing Panca Kesadaran Santri in English Learning: Enhancing Character in Education - Hasanah, Nur; Suryanto, Bradhiansyah Tri (Universitas Nurul Jadid, 2024)
At Nurul Jadid Islamic Boarding School, the panca kesadaran santri—which consists of religious, social, and scholastic aspects—embodies core values. This study looks at how these principles are incorporated into SMK Nurul Jadid's English learning activities and how they show up in lesson planning and instructional strategies. Using a panca kesadaran santri-centered theoretical framework, the research attempts to analyze how it is incorporated into English learning activities and assess how well it is implemented at the school. The study design used is a descriptive-evaluative one that includes documentation, interviews, and observations. The successful incorporation of religious, social, and national/state awareness into lesson planning and learning activities is demonstrated by data analysis. These principles are actively lived by educators and students, supporting a comprehensive approach to character education. The results highlight how crucial it is to match educational methods with the goals and ideals of society. The study provides practical guidance for curriculum development that promotes holistic student development while also making a theoretical contribution to the conversation on values integration in education. It is advised that educational institutions investigate new teaching strategies and include stakeholders in order to foster a values-based culture. Overall, the study emphasizes how panca kesadaran santri can be successfully included into English language learning activities and emphasizes the importance of this practice in developing students' moral character and sense of social responsibility.